You never know : a memoir [large type] - Selleck, Tom, 1945-; Henican, Ellis (DeySt., an imprint of William Morrow, 2024)
In his own voice and uniquely unpretentious style, Tom Selleck brings listeners on his uncharted but serendipitous journey to the top in Hollywood, his temptations and distractions, his misfires and mistakes and, over time, his well-earned success. Along the way, he clears up an armload of misconceptions and shares dozens of never-told stories from all corners of his personal and professional life. His rambunctious California childhood. His clueless arrival as a good-looking college jock in Hollywood (from the Dating Game to the Fox New Talent Program to co-starring with Mae West and escorting her to black-tie social functions). Selleck recounts his personal friendships with a vivid army of A-listers, everyone from Frank Sinatra to Carol Burnett to Sam Elliott, paying special tribute to his mentor James Garner of The Rockford Files, who believed, like Selleck, that TV protagonists are far more interesting when they have rough edges. He also more than tips his hat to the American western and the scruffy band of actors, directors and other ruffians who helped define that classic genre, where Selleck has repeatedly found a happy home. Magnum fans will be fascinated to learn how Selleck put his career on the line to make Thomas Magnum a more imperfect hero and explains why he walked away from a show that could easily have gone on for years longer. Selleck explains how he's struggled to balance his personal and professional lives, frequently adjusting his career to protect his family's privacy and normalcy. His journey offers a truly fresh perspective on a changing industry and a changing world. Beneath all the charm and talent and self-deprecating humor, Selleck's memoir reveals an American icon who has reached remarkable heights by always insisting on being himself.